2006
DOI: 10.1111/j.1365-2966.2006.10580.x
|View full text |Cite
|
Sign up to set email alerts
|

Data analysis on the extrasolar planets using robust clustering

Abstract: We use both the conventional and more recently developed methods of cluster analysis to study the data of extra-solar planets. Using the data set with planetary mass M, orbital period P , and orbital eccentricity e, we investigate the possible clustering in the lnM, lnP , lnP − lnM, e, and lnP − e spaces. There are two main implications: (1) mass distribution is continuous and (2) orbital population could be classified into three clusters, which correspond to the exoplanets in the regimes of tidal, on-going ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…It turns out that they are not able to find structures for EPs. This is in agreement with the analysis of Jiang et al (2006), although it was performed with a very different approach to that adopted here. The main problem of these hierarchies is that either they produce just one or two big clusters and some outliers, or the solution is so nested that the definition of cutoff is too arbitrary and meaningless.…”
Section: Finding the Best Solutionsupporting
confidence: 76%
“…It turns out that they are not able to find structures for EPs. This is in agreement with the analysis of Jiang et al (2006), although it was performed with a very different approach to that adopted here. The main problem of these hierarchies is that either they produce just one or two big clusters and some outliers, or the solution is so nested that the definition of cutoff is too arbitrary and meaningless.…”
Section: Finding the Best Solutionsupporting
confidence: 76%
“…The study of correlations within sub-groups in the cluster analysis done by Jiang et al (2006) and Marchi (2007) also confirms the mass-period correlation. Thus, strictly speaking, the mass and period functions are not two independent power laws.…”
Section: Introductionsupporting
confidence: 64%
“…On the other hand, as pointed in Jiang et al (2006) and in Marchi (2007), the correlation of each group of exoplanets identified in the clustering analysis might be linked with the physical mechanisms more easily. The overall correlations could be more difficult to explain.…”
Section: Mass-period Correlation Coefficientsmentioning
confidence: 83%
“…This confirms that there is a strong eccentricity-period correlation in Cluster Pe1, that is, the planets with larger orbital periods might have larger eccentricities. Furthermore, the characteristics of clusters Pe1 might be related to the tidal interaction based on the clustering results of Jiang et al [10]. However, in Cluster Pe2, there is no eccentricity-period correlation.…”
Section: Application To Extrasolar Planetsmentioning
confidence: 97%
“…However, there is no intracluster correlation in Cluster PM3. According to the clustering results of Jiang et al [10], the characteristics of clusters PM1 and PM2 might relate to the tidal and disc interactions.…”
Section: Application To Extrasolar Planetsmentioning
confidence: 98%